Spitzer Infrared Observations and Independent Validation of the Transiting Super-Earth CoRoT-7b - Fressin, F; Torres, G; Pont, F; Knutson, H; Charbonneau, D; Mazeh, T; Aigrain, S; Fridlund, M; Henze, C; Guillot, T; Rauer, H (2011)
The detection and characterization of the first transiting super-Earth, CoRoT-7 b, has required an unprecedented effort in terms of telescope time and analysis. Although the star does display a radial velocity signal at the period of the planet, this has been difficult to disentangle from the intrinsic stellar variability, and pinning down the velocity amplitude has been very challenging. As a result, the precise value of the mass of the planet - and even the extent to which it can be considered to be confirmed - have been debated in the recent literature, with six mass measurements published so far based on the same spectroscopic observations, ranging from about 2 to 8 Earth masses. Here we report on an independent validation of the planet discovery, using one of the fundamental properties of a transit signal: its achromaticity. We observed four transits of CoRoT-7 b with Spitzer, in order to determine whether the depth of the transit signal in the near-infrared is consistent with that observed in the CoRoT bandpass, as expected for a planet. We detected the transit and found an average depth of 0.426 {±} 0.115 mmag at 4.5 μm, which is in good agreement with the depth of 0.350 {±} 0.011 mmag found by CoRoT. These observations place important constraints on the kinds of astrophysical false positives that could mimic the signal. Combining this with additional constraints reported earlier, we performed an exhaustive exploration of possible blends scenarios for CoRoT-7 b using the BLENDER technique. We are able to rule out the vast majority of false positives, and the remaining ones are found to be much less likely than a true transiting planet. We thus validate CoRoT-7 b as a bona-fide planet with a very high degree of confidence, independently of any radial-velocity information. Our Spitzer observations have additionally allowed us to significantly improve the ephemeris of the planet.